Effect of LC3 Homologues on Cytoplasmic TDP-43, Stress Granules and Contents of Small Extracellular Vesicles - Tristani, Angelica (Université d'Ottawa | University of Ottawa, 2024)
Autophagy is a crucial process to maintain protein quality control and degrade cargo in the cell. Aberrant autophagy plays a crucial role in the pathogenesis of various neurodegenerative diseases, includinAmyotrophic Lateral Sclerosis (ALS). ALS is the most common motor neuron disease, with 90% of cases occurring sporadically and 10% being familial. So far, there is no known cure for ALS; most therapeutics alleviate symptoms or delay their onset. ALS is primarily characterized by RNA binding proteins (RBPs) such as TDP-43, which is associated with 97% of cases.1 In fact, aberrant dynamics of RBPs have been shown to lead to their aggregation and interaction with stress granules in ALS. 2 More specifically, stress granules unable to disassemble may persist in the cell, then requiring elimination by autophagy. 2,3 However, in ALS, we often find impaired autophagy and insufficient degradation of RBPs, leading to aggregate accumulation in the cytoplasm.3 For this reason, fostering the autophagy pathway as a therapeutic method in ALS can potentially induce turnover and elimination of these pathogenic proteins, preventing their accumulation and ultimately cell death. Specifically, LC3 homologues offer a unique interest due to their direct involvement with later stages of autophagy, their selectivity, and their possible roles beyond autophagy. For the latter, LC3 has been implicated in secretory autophagy pathways, such as loading cargo for elimination into extracellular vesicles (EVs) to compensate for states of lysosomal inhibition. 4,5 Our goal was to analyze the effects of LC3 homologues in degradation of TDP-43 and stress granules and explore the involvement of LC3 stress granule protein loading into small EVs. Using high-throughput imaging microscopy, we compared the effects between different LC3 knockdowns on stress granule levels and cytoplasmic TDP-43. This allowed us to identify which LC3 homologues significantly impact clearance of these ALS-related substrates. The effect of LC3 knockdown on cytoplasmic TDP-43 degradation is unclear; however, GABARAPL1 offers a promising role in the degradation of stress granules. Further investigation into the role of GABARAPL1 in stress granule clearance may offer therapeutic potential in ALS models to prevent the accumulation of stress granules. Lastly, knockdown of all LC3 homologues showed increased loading of stress granule proteins into EVs. In previous studies, LC3 appeared to be involved in packing RBPs and stress granule proteins into EVs; however, we saw opposing results in our mass spectrometry data. Analysing EV content in cells knocked down for LC3/GABARAP knockdown allowed us to depict the influence that LC3s have in EV cargo loading, specifically concerning stress granule proteins.
Keywords: Autophagy; ALS